Odpowiedzi

Najlepsza Odpowiedź!
2009-11-27T10:44:34+01:00
A)

√2 √7
__ * ___ =
√7 √7

√2*√7
_______ =
7

√14
_____
7
B)

√2 3 +2√2 3√2 +4
_____ * ______ = _______ = 3√2 + 4
3-2√2 3+ 2√2 1
2009-11-27T10:45:51+01:00
√2
__
√7

mnożymy licznik i mianownik przez √7
czyli będzie
√7 *√2
------------
√7 *√7

czyli √14/7

b)mnożymy licznik i mianownik przez 3+2 √2

√2
_____
3-2 √2

√2 *(3+2 √2)
---------------
(3+2 √2)(3-2 √2)


3√2+4
--------
9-8


=3√2+4
2009-11-27T10:47:46+01:00
A)
√2 (√2)(√7) √14
__=________=____
√7 (√7)(√7) 7

b)
√2 (√2)(3+2√2) 3√2+4
_____=______________=__________= 3√2+4
3-2√2 (3-2√2)(3+2√2) 9-8